Stability of Antenna-Column of Neglectable Own Weight in Design of Wireless Traffic Network - Saucha, Juraj; Radoš, Jerko; Badanjak, Dragan (Promet - Traffic&Transportation, 2012)
The paper deals with the problem of elas1ic stability of antenna-column ofneglec/able own weight subjected to the actionof effective load on its lop. The determination of critical bucklingforce is based upon the derived exact solution to !he equilibriumequation of the column of continuously variable crosssection loaded with conswnl compressive force.